Characterisation of thermal barrier coatings - Yeow, Elizabeth Maria Hui Shi (2015)
High pressure turbine blades in aircraft are subject to high temperatures, often above 1000˚C, during in-flight operations, thus the base metal requires protection from oxidation by an aluminide coating, which generates a protective oxide layer on top of itself. In this study, research was carried out to develop a standard, via oxidation experiments and subsequent characterisation of the oxide layer, by which the coating of turbine blades could be categorized as in need of re-coating. After carrying out preliminary testing using uncoated iron alloys, the experimental methods for nickel alloys as the base metal for the coated samples were determined and carried out. The results of isothermal oxidation of nickel alloy samples show that, for a holding time of 5h, oxide layer growth and the formation of the stable α phase of aluminium oxide Al2O3 starts even at lower temperatures of 750˚C, although it is only the major phase when the sample is heated to 1100˚C for 100h. The aluminium content in the coating also declined with heating temperature and holding time due to both outward diffusion to form the coating, and inward diffusion to the substrate. In addition, it was found that heating to temperatures of up to 1100˚C for 100h produced an oxide layer of up to 6.9μm. These observations are sufficient in monitoring the growth pattern of the oxide, although not its depletion. Neither a decrease in oxide layer thickness, nor a decline in the aluminium content of the sample to below the acceptable limit, was observed with increasing temperature and heating time. This work is carried out in collaboration between NTU, Advanced Remanufacturing and Technology Centre (ARTC) and a company in the aerospace industry.